Study of fine particle peening based on the fully coupled thermo-mechanical method - Boyu Zhang; Zhengwei Wang; Yongyong He; Taohan Sun (Journal of Materials Research and Technology)
A fully coupled thermo-mechanical model was constructed to investigate the temperature evolution mechanism during the fine particle peening process. The relative errors between experimental and simulated temperature results didn't exceed 6.9 %. The influence of air pressure, particle diameter, and initial temperature at a coverage rate of 200 % on PEEQ, surface roughness, temperature distribution, and residual compressive stress was systematically investigated. The results indicate that the surface temperature reaches a saturation point and stops increasing further during the fine particle peening process. The thermo-mechanical coupling model predicts a higher PEEQ and lower residual compressive stress than the conventional model. As the initial temperature increases, there is minimal variation in residual compressive stress, while surface roughness increases significantly. Therefore, it is recommended that 18Cr2Ni4WA steel not be heated during shot peening or fine particle peening.